81 Innovative Management of Low Risk Patients with Chest Pain Presenting to The Emergency Department. (3rd June 2016) - Pope, Michael; Pugh, Nichola; Gilpin, Thomas; Farrell, Tom
Abstract : Introduction: Chest pain is one of the most common symptoms amongst patients presenting acutely to secondary care. The Rapid Access Cardiology Clinic (RACC) was established at our hospital with the aim of reducing admissions of low risk patients presenting to the emergency department (ED) and medical assessment unit (MAU) with chest pain of presumed cardiac origin. This is designed as a 'next day' consultant led service running 5 days a week with access to same day echocardiography, invasive and CT coronary angiography. This evaluation aimed to assess safety, clinical outcomes and service efficiencies achieved from this service. Methods: We carried out a retrospective analysis of sequential patients referred to the RACC with chest pain over a one month period. Data was collected for investigations performed, need for revascularisation, re-presentations and adverse events over 3 months of follow up. In addition to this, we reviewed the admission notes to evaluate what alternative management pathways may have been used in order to assess the number of overnight admissions, outpatient appointments or GP services that were saved. Results: 56 patients were seen in the clinic in the one month analysed. Of the 56 patients, 25 (44.6%) were discharged directly from RACC with no investigations, 4 (7.1%) had no investigations but had cardiology clinic follow-up, and 27 (48.2%) required further cardiac investigations. 23 of this 27 (85.2%) had invasive tests, 3 (11.1%) had non-invasive and 1 had both (3.7%). 4 of these were found to be abnormal and subsequently 1 was referred for coronary artery bypass grafting. The remainders were managed medically. Re-presentations were few, with 1 patient attending ED over a weekend whilst waiting for the appointment with further troponin negative chest pain. There were 3 re-presentations within 3 months following RACC review. Of these, 1 admission was due to a headache and syncope, one was due to angina whilst waiting for coronary angiography and the third was due to further troponin negative chest pain. There were no adverse events. It was estimated that 33 overnight admissions were avoided. Furthermore, 49 of the patients referred may alternatively have been managed via the primary care fast access chest pain service. This would have required a GP appointment and referral therefore involving significant primary care resources. Conclusions: The RACC model provides a safe and effective pathway for diverting care of low risk patients presenting acutely with chest pain of presumed cardiac origin to the outpatient department. The low rate of re-presentations without any adverse events demonstrates the safety of this approach. Clinical outcomes within the 3 months were excellent with only 1 patient requiring revascularisation. Furthermore, there were significant service efficiencies delivered with benefits evidenced across both primary and secondary care.